2017
DOI: 10.1155/2017/9045608
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine to Help Nerve Regeneration in a Rat Sciatic Nerve Injury Model

Abstract: Background Several studies have shown that dexmedetomidine (DXM), a selective α2-adrenoceptor agonist, also has neuroprotective effects. However, its effect on impaired peripheral nerve regeneration has not been studied. Materials and Methods Forty-five Sprague-Dawley rats were randomly assigned to three groups: group 1 (control SHAM), group 2 (sciatic nerve injury + normal saline), and group 3 (sciatic nerve injury + DXM). The rats of group 3 were subdivided into the following three groups: DXM 0.5, 6, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, Dex protected cerebral against hypoxic-ischaemic damage by elevating microRNA-140-5p via the Wnt/β-catenin signaling pathway (Han et al, 2018). A recent study reported that Dex could help to axon regeneration in a rat sciatic nerve injury model (Jeong et al, 2017). Nevertheless, the effect of Dex on immature brain remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dex protected cerebral against hypoxic-ischaemic damage by elevating microRNA-140-5p via the Wnt/β-catenin signaling pathway (Han et al, 2018). A recent study reported that Dex could help to axon regeneration in a rat sciatic nerve injury model (Jeong et al, 2017). Nevertheless, the effect of Dex on immature brain remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A single operator performed all procedures to minimize surgical and injection rate variability. All animals were euthanized via CO 2 asphyxiation followed by cervical dislocation 6 weeks postoperatively, a timepoint used in several studies to evaluate nerve regeneration both functionally and histologically . Gastrocnemius muscles harvested from both the operated (right) and non‐operated (left) hindlimbs of all rats after euthanasia were imaged (Nikon D3400 digital camera) and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…All animals were euthanized via CO 2 asphyxiation followed by cervical dislocation 6 weeks postoperatively, a timepoint used in several studies to evaluate nerve regeneration both functionally and histologically. [22][23][24] Gastrocnemius muscles harvested from both the operated (right) and non-operated (left) hindlimbs of all rats after euthanasia were imaged (Nikon D3400 digital camera) and weighed. Denervated muscles were normalized against their non-operated contralateral counterparts.…”
Section: Sciatic Nerve Injury and Asc Injection Intomentioning
confidence: 99%
“…In order to create a crush, the sciatic nerves are subjected to the mechanical consistent compression using a pair of sterile Watchmaker's forceps for 30 (Wood et al, ) and 15 s (Ramli, Aziz, Mohamad, Abdulahi, & Sanusi, ), or clamping by 100‐gf microclamp for 10 s (Hong et al, ), and using a curved Kelly hemostatic clamp for 30 s with a clamping force of approximately 40 N before its bifurcation (Jeong et al, ).…”
Section: The Necessary Work Before During and After The Conduit Impmentioning
confidence: 99%